Extracting Appropriate Nodal Marginal Prices for All Types of Committed Reserve - Akbary, Paria; Ghiasi, Mohammad; Pourkheranjani, Mohammad Reza Rezaie; Alipour, Hamidreza; Ghadimi, Noradin (Computational economics, 2019)
This paper proposes a framework to extract appropriate locational marginal prices for each type of reserve (up-/down-going reserves at both generation- and demand-sides). The proposed reserve pricing scheme accounts for the lost opportunity of selling the convertible products (energy and reserve). The fair prices can be obtained for capacity reserves applying this framework, since this framework assigns the same prices to the same services provided at the same location. The proposed reserve pricing scheme provides all the market participants with the appropriate signals to modify their offers according to the system operator requirements. The pricing problem is decomposed to different hourly sub-problems considering the bounding constraints. To show the effectiveness of the proposed algorithm, it is applied to the IEEE reliability test system and the results are discussed.